Measurement Invariance of the UPPS-P Impulsive Behavior Scale Across Age and Sex Across the Adult Life Span. (April 2020) - Argyriou, Evangelia; Um, Miji; Wu, Wei; Cyders, Melissa A.
Impulsive personality is a widely used construct for the prediction of multiple clinical problems; however, research has often disregarded important differences in its conceptualization and measurement across age and sex. The goals of this article are to test the invariance of, to compare mean differences in, and to examine the differential validity of the Urgency (negative), Premeditation (lack of), Perseverance (lack of), Sensation Seeking, with added subscale of Positive Urgency (UPPS-P) Impulsive Behavior Scale across adult age and sex. The data for this study were obtained from 799 participants in the Nathan Kline Institute's Rockland Sample. Multigroup invariance analysis indicated full invariance of the UPPS-P Impulsive Behavior Scale across age and sex. However, invariance analysis as a function of age using Multiple-Indicators Multiple-Causes modeling identified three items with differential item functioning. Sensation Seeking was higher in males and lower as age increased. In general, age and sex did not moderate the relationships between UPPS-P traits and risk-taking behaviors, with the exception of cannabis use. Overall, the results of this study support that the UPPS-P scale can be validly used to assess and compare impulsive personality across the adult life span and sex. We suggest the removal of Items 5, 28, and 51 when using the UPPS-P with older adults to be overly cautious to age invariance effects.